CHEMICAL CHARACTERISTICS OF MULTIFLORAL WILD AND APIARY HONEY FROM WESTERN GHATS OF KARNATAKA - M. V. BALASUBRAMANYAM (The Bioscan, 2011)
Multifloral honey of indigenous honeybee species, Apis dorsata, Apis florea (wild) and Apis cerana (apiary) from three diverse zones of Western Ghats of Karnataka during April 2010 to March 2011. Chemical characteristics of moisture, TRS, NRS, L/D ratio, ash, acidity and pH were determined. Honey of Apis dorsata exhibit more moisture (23.55%), acidity (0.518%), ash (1.49%) and pH (0.503) compared to honey of Apis florea and Apis cerana honey. Similarly, Apis cerana honey displays more L/D ratio (1.19) than Apis dorsata (1.12) and Apis florea (1.13). However, TRS and NRS of honey among three honeybee species demonstrated considerable variations. Excluding L/D ratio and acidity all parameters tested were significant at p<0.01and p<0.05. Results of the study confirmed the quality of honey of Apis cerana, Apis florea and Apis dorsata were equally good with minor changes in the composition which are discussed in ensuing paper.